Low-Grade Surface Osteosarcoma of the Temporal Bone in Paediatric Patients: A Case Report and Literature Review. (June 2019) - Villemure-Poliquin, Noémie; Trudel, Mathieu; Labonté, Sebastien; Blouin, Valérie; Fradet, Gaétan
Purpose of the study: Primary osteosarcoma of the temporal bone is an exceedingly rare pathology in the paediatric population. As of now, only 3 cases have been reported in the English literature. We describe the additional case of a 16-year-old girl with an osteosarcoma of the mastoid bone. This study aims to report a rare paediatric case of low-grade surface osteosarcoma of the temporal bone. Materials and methods used: A literature review was performed to better understand paediatric osteosarcomas of the head and neck region, to optimize their investigation, to describe their histopathological and radiological characteristics, and to establish the optimal modalities of medical and surgical treatments. The research of previous published data was done using PubMed and Embase library with the keywords mentioned below. Results: The patient presented with a rapidly progressive left retroauricular lesion over a 3-week period. Radiological studies demonstrated aggressive and invasive features. An open biopsy followed and confirmed the diagnosis of a low-grade surface osteosarcoma. In accordance with the multidisciplinary team, we decided to perform a complete surgical resection with wide surgical margins. We did not administer any adjuvant therapies. A control computed tomography (CT) scan obtained 26 months postoperatively still showed no signs of recurrence. Conclusion: Osteosarcomas are aggressive malignant neoplasms found in the head and neck region in only 6% to 10% of cases. They represent approximately 1% of head and neck cancers, and these are generally high-grade lesions. Temporal bone involvement is rare, particularly for low-grade lesions in paediatric patients. In addition to reporting the fourth paediatric case of primary temporal bone osteosarcoma, this study describes its specific clinical, histopathological, and radiological findings, to improve the management and the prognostic of patients affected with this particular clinical entity.